Expressão heteróloga e modelagem de uma enzima lipolítica utilizando a abordagem metagenômica - Garcia, Rosmeriana Áfnis Marioto [UNESP] (2014)
The metagenomics is a powerful tool in the discovery of new microbial genes with biotechnological potential, they are not necessary traditional cultivation techniques. With increasing demand for enzymes in the market this technique has been widely used for the discovery of new genes encoding microbial lipases and esterases widely used in biotechnological processes such as the production of detergents, biodiesel and bioremediation. In previous work, coding sequences for lipolytic enzymes were prospected in 4224 clones from a metagenomic DNA library from a microbial consortium obtained from soil contaminated with petroleum hydrocarbons, located in the city of Ribeirão Preto - São Paulo - Brazil, obtaining 30 clones with possible lipase activity on tributyrin. In this study, one clone was selected after testing in a Petri dish with Tributyrin to build a sub-library, with 480 subclones. Sequencing was performed on ABI PRISM 3100 instrument and analyzed “contig”s obtained in the ORF finder from the National Center for Biotechnology Information (NCBI, Bethesda, Maryland, USA). It was possible to identify a gene of 1032 bp, 344 amino acids, termed ORF2, encoding a lipolytic enzyme with 94% identity with a hydrolase from Pseudomonas denitrificans (YP_007656829.1). The sequences representing eight families of lipolytic enzymes and Arpying proposed by Jaeger (1999) were extracted from the NCBI database and compared with the sequence of ORF2, allowing affirm that this enzyme is a new member of the family V bacterial lipolytic enzymes . The encoder ORF2 gene was cloned into pET28a expression vector and overexpressed in Escherichia coli BL21 (D3). The soluble protein fraction was analyzed by polyacrylamide (SDS-PAGE) gel in denaturing condition. The lipolytic activity of the recombinant protein bands on the SDS-PAGE gel was confirmed by a zymogram indicating its functionality in a specific substrate. Three-dimensional modeling was also ...